Design of Computer Recognition System Based on Graphic Image - Luo, Qun; Liu, Zhendong; He, Ruiying (Journal of Applied Data Sciences, 2023)
With the advancement of computer technology and the rapid development of the Internet, every bit of life has begun to become electronic. The recognition of informatized graphic images is particularly important. The image is collected through graphic images and the elements in the image are detected and recognized autonomously. Some characteristic elements of the image are used to identify and correspond to the characteristics in real life. This article first analyzes the research and discussion on the accuracy of the image and graphic information. After reading it through the computer, the image quality is improved accordingly. Finally, the design of the computer recognition system based on the graphic image is obtained.